Pembelajaran PAI Ranah Afektif dalam Membentuk Etika Islam Siswa di SMA Negeri 8 Kediri - wa'dullah wa'dullah (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2016)
Islamic education has a major contribution in fortifying students' morale in everyday life. Education simply means the process of changing the attitude and behavior of a person or group in an effort to mature human beings through the efforts of teaching and training. Therefore, the success of an education implementation will be largely determined by the learning. For that, learning PAI Affective domain is very utgen in shaping Islamic ethics, researchers focus on students in SMA Negeri 8 Kediri. The research method used qualitative approach with descriptive research type and case study. The research was conducted at SMA Negeri 8 Kediri. The data source is people, place, and paper. Data collection techniques used observation, interviews, and documentation. The analysis uses data reduction, data presentation and conclusion. The results of this study revealed that: 1) Efforts of teachers in improving Islamic ethics in SMA Negeri 8 Kediri, namely: religious habituation. application of Islamic uniform. creates a religious atmosphere. advice or motivation and punishment. approach and good communication to students. Islamic education teachers should be good role models for students. build good relationships with parents. 2) Factors that support, namely, awareness and willingness of students. The sense of responsibility of teachers of Islamic religious education in schools. A conducive school environment. Interactions of students in everyday life. Supportive infrastructure. The inhibiting factors include, the background of the less supportive students, the community environment (Student Association). The lack of a sense of solidarity between religious teachers and teachers in the field of public studies and the increasingly sophisticated influence of technology.